2008
DOI: 10.1037/0882-7974.23.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Multilingualism and cognitive state in the oldest old.

Abstract: In this study, the authors examined whether the number of languages a person speaks predicts performance on 2 cognitive-screening tests. Data were drawn from a representative sample of the oldest Israeli Jewish population (N = 814, M age = 83.0 years; SD = 5.4) that was interviewed first in 1989 and then twice more within the following 12 years. Cognitive state differed significantly among groups of self-reported bilingual, trilingual, and multilingual individuals at each of the 3 interview waves. Regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
149
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(171 citation statements)
references
References 40 publications
17
149
2
3
Order By: Relevance
“…Notably, Kave et al (2008), with a follow-up study of 814 healthy old man over a period of 13 years, found that the number of languages they spoke could predict the performance on various cognitive tests after controlling for some demographic variables (such as age, gender, place of birth, age and education level). They proposed for the first time that the more languages old people spoke on regular basis, the higher their cognitive levels would be [21]. It is known as the cumulative effect of languages, which is consistent with the results of Luxembourg's study that mastering one more language would increase the probability of protection against cognitive impairment by more than four times (of course, a threshold existed) and the earlier they became multilingual, the greater the protection would be [25].…”
Section: Bilingualism Contributing To Better Cognitive Ability In Heasupporting
confidence: 77%
See 1 more Smart Citation
“…Notably, Kave et al (2008), with a follow-up study of 814 healthy old man over a period of 13 years, found that the number of languages they spoke could predict the performance on various cognitive tests after controlling for some demographic variables (such as age, gender, place of birth, age and education level). They proposed for the first time that the more languages old people spoke on regular basis, the higher their cognitive levels would be [21]. It is known as the cumulative effect of languages, which is consistent with the results of Luxembourg's study that mastering one more language would increase the probability of protection against cognitive impairment by more than four times (of course, a threshold existed) and the earlier they became multilingual, the greater the protection would be [25].…”
Section: Bilingualism Contributing To Better Cognitive Ability In Heasupporting
confidence: 77%
“…More importantly, positive effects are assumed to extend to the elderly, helping ward off age-related decline of the cognitive levels [19][20][21][22]. For example, by comparing the performances of the middle-aged and old bilinguals with those of their monolingual counterparts in Simon task and the Visual Stroop task (executive control), Bialystok et al found bilingual advantage in both groups, especially in old age group [19,23].…”
Section: Bilingualism Contributing To Better Cognitive Ability In Heamentioning
confidence: 99%
“…The current findings are consistent with this literature. However, interestingly, the cognitive skills that were identified as potential predictors of independent language learning success (digit span and orientation) have also been identified as potential cognitive consequences of long-term bilingualism in older adults (e.g., Kavé et al, 2008). This leaves open the possibility for a somewhat broader maintained ability for language learning in bilingual and multilingual older adults (e.g., Antoniou et al, 2013).…”
Section: Summary Future Directions and Conclusionmentioning
confidence: 99%
“…An important factor which may influence the relationship between bilingualism and the development of dementia is the level of proficiency in the second language ( Antoniou, Gunasekera, & Wong, 2013;Gollan et al, 2011;Kavé, Eyal, Shorek, & Cohen-Mansfield, 2008;Kaushanskaya & Prior, 2015;Zied et al, 2004). For instance, Zied and colleagues (2004) reported that balanced bilinguals (who use both languages proficiently) performed significantly better on a Stroop task, measuring executive function, than unbalanced bilinguals (who were less proficient in one language).…”
Section: Definition Of Bilingualism Used In Studies Language Proficiencymentioning
confidence: 99%